Analysing the impact of living in a rural setting on the presentation and outcome of colorectal cancer. A prospective single centre observational study. Issue 6 (December 2020) - MacVicar, E.; Ritchie, D.; Murchie, P.; Parnaby, C.; MacKay, C.; Ramsay, G.
Abstract: Introduction: Approximately 17% of the Scottish population lives in a remote or rural location. Current research is contradictory as to whether living a rural location leads to poorer outcomes or affects survival from colorectal cancer (CRC). We aimed to assess if living in a rural location influences outcome of CRC patients in 21st century UK medicine. Methods: A prospective single-centre observational study was conducted. All patients who underwent resection for colorectal cancer 2005–2016 in NHS Grampian were included. Patients were split into two groups for comparison (urban post-code vs rural) using the Scottish government two-tier classification system. Tumour location, one-year survival, lymph node involvement and extra-mural vascular invasion was recorded and compared between the groups. Results: Of 2463 patients, 843 (34.2%) lived in a rural area. Rural patients were more likely to be detected through screening (17.4% versus 14.6%, p = 0.04). There were no differences in pathology between rural and urban groups if detected through screening. However, rural patients detected through symptomatic pathways were more likely to be node positive p = 0.015. On multivariable analysis, rurality did not independently predict for node positive presentation. Furthermore, there were no differences in cumulative survival between the two groups. Conclusion: Although there were some differences in pathological characteristics between rural and urban patients, place of residence did not independently predict for outcome in this cohort. Rurality had previously been shown to impact on outcome up to 20 years ago. Improvements in infrastructure and rural healthcare may have influenced this change.